HUBUNGAN KONFORMITAS TERHADAP PERILAKU FEAR OF MISSING OUT (FOMO) GEN Z PADA PELUNCURAN PRODUK SOMETHINC DI SOSIAL MEDIA TIKTOK - RIZKYANADA, DINDA BRIGITTA; Warastri, Annisa (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
This study aims to examine the relationship between Conformity and Fear of Missing Out (FoMO) among Generation Z consumers of Somethinc products on the TikTok platform in Yogyakarta. Using a quantitative approach with a correlational design, this study involved 98 respondents aged 13–28 years who had purchased Somethinc products, had a TikTok account, and resided in the Special Region of Yogyakarta. Data collection was conducted online through Google Forms using a Conformity scale (36 items) and a Fear of Missing Out (FoMO)scale (39 items) adapted from previous studies. Data analysis was performed using normality tests (Kolmogorov-Smirnov), linearity tests, and Pearson's Product Moment correlation. The results showed that the majority of respondents had high levels of Conformity (63%) and Fear of Missing Out (FoMO) (66%). There was a positive and significant relationship between Conformity and Fear of Missing Out (FoMO) (r = 0.610; p = 0.000), with Conformity contributing 37.2% to Fear of Missing Out (FoMO). These findings support the hypothesis that the higher an individual's Conformity, the higher their tendency to experience Fear of Missing Out (FoMO) in the context of digital consumption on TikTok. This study provides theoretical contributions to understanding the psychological dynamics of Generation Z as well as practical implications for ethical marketing and digital literacy education.